DRYING AND BURNING OF NICKEL HYDROCARBONATE - Akhunbaev Adil Alimovich; Askarov Khasanzhon Abdukakhorovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The article describes the process of heat treatment - drying and roasting of finely dispersed nickel bicarbonate in a contact drum apparatus with a rapidly rotating rotor. A drying curve and a drying rate curve obtained experimentally are given. On the basis of general ideas about drying and its laws, the physical picture of the process is considered according to the stages occurring in the drying unit.